2017
DOI: 10.1002/14651858.cd009242.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill interventions in children under six years of age at risk of neuromotor delay

Abstract: Angulo-Barroso, R. (2017). Treadmill interventions in children under six years of age at risk of neuromotor delay. Cochrane database of systematic reviews (Online), (7), [CD009242].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 149 publications
1
29
0
1
Order By: Relevance
“…This adjunctive approach to EE and task-specific training is supported by evidence that such combination therapies augment recovery of fine-motor skills that normally do not benefit from EE alone, in both models of focal ischemia (Biernaskie and Corbett, 2001 ) and intracerebral hemorrhage (MacLellan et al, 2011b ; Caliaperumal and Colbourne, 2014 ). Additional combinations of EE with various pharmacological agents has also yielded promising synergistic results; however, this work is still in its infancy (Corbett et al, 2014 ; Mering and Jolkkonen, 2015 ; Malá and Rasmussen, 2017 ). Our previous work has demonstrated that the combination of EE, task-specific reaching and growth factor administration accelerates the rate of recovery of fine motor dexterity (Jeffers et al, 2014 ).…”
Section: Benefits Of Environmental Enrichment On Functional Recovery mentioning
confidence: 99%
“…This adjunctive approach to EE and task-specific training is supported by evidence that such combination therapies augment recovery of fine-motor skills that normally do not benefit from EE alone, in both models of focal ischemia (Biernaskie and Corbett, 2001 ) and intracerebral hemorrhage (MacLellan et al, 2011b ; Caliaperumal and Colbourne, 2014 ). Additional combinations of EE with various pharmacological agents has also yielded promising synergistic results; however, this work is still in its infancy (Corbett et al, 2014 ; Mering and Jolkkonen, 2015 ; Malá and Rasmussen, 2017 ). Our previous work has demonstrated that the combination of EE, task-specific reaching and growth factor administration accelerates the rate of recovery of fine motor dexterity (Jeffers et al, 2014 ).…”
Section: Benefits Of Environmental Enrichment On Functional Recovery mentioning
confidence: 99%
“…[16][17][18] Further, a recent update of the Cochrane review concluded that treadmill training interventions in children with CP under 6 years of age may accelerate motor skill attainment. 19 While evidence points towards beneficial effects of gait training, because of the lack of high-quality randomized controlled trials, until now there has been insufficient evidence to recommend its use in a clinical setting. Previous systematic reviews were limited by their focused scope in the definition of gait training and often reported only limited gait outcomes, as such not incorporating all the benefits that gait training in children and young adults with CP could bring.…”
mentioning
confidence: 99%
“…Previous systematic reviews have focused on the use of partial body weight support treadmill training (PBWSTT), ultimately concluding that it is a safe and feasible treatment option for children with CP and with positive evidence reported . Further, a recent update of the Cochrane review concluded that treadmill training interventions in children with CP under 6 years of age may accelerate motor skill attainment . While evidence points towards beneficial effects of gait training, because of the lack of high‐quality randomized controlled trials, until now there has been insufficient evidence to recommend its use in a clinical setting.…”
mentioning
confidence: 99%
“…Some asymmetries are normal for human movement, however some can be impacted for various reasons. For parents and pediatricians as well as physiotherapists, the wide spectrum of factors influencing child development should be known for proper movement analysis [ 1 ]. Persistent asymmetrical tonic neck reflex (ATNR) is one of the factors that can impact child development.…”
Section: Introductionmentioning
confidence: 99%
“…Noticing the wide range of child developmental fields impacted by primitive reflexes (PRs), the authors investigated if the walking pattern is also regulated by and dependent on the degree of PR activity. Because gait is a complex motion, which involves the whole body, dependence on the reflex reaction through muscle tension may influence gait parameters [ 1 , 3 , 9 , 10 ]. Thus, the aim of the study was to find if there is an ATNR impact on the symmetry parameters of the gait.…”
Section: Introductionmentioning
confidence: 99%